Dimerumic acid and deferricoprogen produced by Monascus purpureus attenuate liquid ethanol diet-induced alcoholic hepatitis via suppressing NF-κB inflammation signalling pathways and stimulation of AMPK-mediated lipid metabolism. (September 2019) - Lai, Jhao-Ru; Ke, Bo-Jun; Hsu, Ya-Wen; Lee, Chun-Lin
Graphical abstract: Highlights: DMA and DFC prevented alcoholic hepatitis. DMA and DFC suppressed alcohol-induced inflammation signalling pathways. DMA and DFC stimulated of AMPK-mediated lipid metabolism in liver. Abstract: Ethanol metabolism causes oxidative stress, inflammation, and then results in steatosis and liver injury. Monascus -fermented products and its secondary metabolites perform liver protection by anti-inflammation, anti-oxidatiion and protecting the liver. In this study, dimerumic acid and deferricoprogen produced by Monascus purpureus were first to investigate the protection against alcoholic liver disease. C57BL/6J mice were fed Lieber-DeCarli liquid ethanol diet and orally given dimerumic acid and deferricoprogen daily for 6 weeks. The mechanisms involved in antioxidative system, anti-inflammatory, and lipid modulation were investigated. The results showed that dimerumic acid and deferricoprogen performed liver protection against ethanol-diet. The two compounds increased anti-oxidative enzymes activities (catalase, SOD, and GPx), suppressed pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, NF-κB, iNOS, and COX-2) via upregulating PPAR-γ and Nrf-2 pathway and inhibiting p-ERK1/2, and modulated lipid metabolism by upregulating AMPK and PPAR-α pathway. Therefore, dimerumic acid and deferricoprogen were both high potential hepatoprotective compounds produced by Monascus purpureus.